2018
DOI: 10.1080/02687038.2018.1517406
|View full text |Cite
|
Sign up to set email alerts
|

A concise patient reported outcome measure for people with aphasia: the aphasia impact questionnaire 21

Abstract: Background: There are many validated and widely used assessments within aphasiology. Few, however, describe language and life with aphasia from the perspective of the person with aphasia. Across healthcare, patient experience and user involvement are increasingly acknowledged as fundamental to person-centred care. As part of this movement, Patient Reported Outcome Measures (PROMs) are being used in service evaluation and planning. Aims: This paper reports the quantitative aspects of a mixed methods study that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…All tools included in the selected studies are considered PRO (patient-reported outcome) or PROMs (patient-reported outcome measures). PRO or PROMs are scales or measurements of the health status of the patients, provided directly by the patient, without the interpretation or involvement of a physician or any other rehabilitation or health specialist [ 26 ]. The involvement of PWA in QoL and AIR tools was analyzed and presented as reported in the selected published studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All tools included in the selected studies are considered PRO (patient-reported outcome) or PROMs (patient-reported outcome measures). PRO or PROMs are scales or measurements of the health status of the patients, provided directly by the patient, without the interpretation or involvement of a physician or any other rehabilitation or health specialist [ 26 ]. The involvement of PWA in QoL and AIR tools was analyzed and presented as reported in the selected published studies.…”
Section: Resultsmentioning
confidence: 99%
“…From the 10 selected studies reporting on the development of AIR-Q, only four involved PWA in their creation. These tools were (1) the ALA—Assessment for Living with Aphasia in the study of Simmons-Mackie et al [ 44 ], (2) the ACOM—Aphasia Communication Outcome Measure of Hula et al [ 45 ], (3) the MOSE—Measurement of Stroke Environment in the study of Babulal and Connor [ 8 ], and (4) the AIQ—Aphasia Impact Questionnaire of Swinburn et al [ 26 ]. All four AIR-Qs were based on a conceptual framework: The ALA, ACOM, and the MOSE (75%) were constructed on the ICF framework, [ 6 ] whereas the AIQ followed the Social Model of Disability [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational profiles that aim to measure functional communication in aphasia include the Communicative Effectiveness Index (CETI; Lomas et al, 1989), the Assessment of Communicative Effectiveness in Severe Aphasia (ACESA; Cunningham et al, 1995), the Functional Outcome Questionnaire for Aphasia (FOQ-A; Ketterson et al, 2008), the Communicative Activity Log (CAL; Pulvermüller & Berthier, 2008), the Communication Outcome after Stroke, client and carer version (COAST and carer COAST; Long, Hesketh, & Bowen, 2009), and the Aphasia Communication Outcome Measure (ACOM; Hula et al, 2015). Measures such as the COAST have expanded their definition of functional communication outcome to include measures of the impact of the communication impairment on the client's life (similar examples are the Aphasia Impact Questionnaire-21, Swinburn et al, 2018;Swinburn & Byng, 2006). The criticism for observational profiles as discussed in the previous section also applies here: they are considered to be subjective and indirect measures of functional communication (Blomert et al, 1987;van der Meulen et al, 2010), including the fact that for these profiles, communication is judged on the basis of indirect observation (i.e., memory of multiple conversations that have previously been observed).…”
Section: Observational Profiles (Client or Proxy Rated)mentioning
confidence: 99%